2018
DOI: 10.5205/1981-8963-v12i12a237459p3500-3505-2018
|View full text |Cite
|
Sign up to set email alerts
|

Reflexão sobre a necessidade de educação permanente em terapia nutricional

Abstract: RESUMO Objetivo: refletir sobre a terapia nutricional enteral e a importância da assistência de enfermagem ao paciente. Método: trata-se de um estudo qualitativo, do tipo reflexivo, baseado em revisão de literatura sobre terapia nutricional enteral, entre os anos de 1998 a 2018, além da percepção dos autores a respeito do assunto. Realizou-se a sistematização dos dados pela técnica de Análise de Conteúdo. Apresentaram-se os resultados em duas categorias: “Indicação de terapia enteral e a técnica de introdução … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
5
0
4
Order By: Relevance
“…Previous research has highlighted the important role played by the nursing team in the prevention of adverse events related to enteral nutrition. The results showed that these professionals were able to recognize potential risks and intervene early, contributing to the maintenance of life (Carrasco et al, 2018). However, flaws in nursing care are still found due to theoretical limitations and/or negligence (Medeiros et al, 2015), with divergence between what is practiced and what is recommended in national (Brasil, 2000) and international (Boullata et al, 2017) enteral nutrition guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted the important role played by the nursing team in the prevention of adverse events related to enteral nutrition. The results showed that these professionals were able to recognize potential risks and intervene early, contributing to the maintenance of life (Carrasco et al, 2018). However, flaws in nursing care are still found due to theoretical limitations and/or negligence (Medeiros et al, 2015), with divergence between what is practiced and what is recommended in national (Brasil, 2000) and international (Boullata et al, 2017) enteral nutrition guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Domain 02, which addressed the technique for the insertion of the feeding tube, had the highest number of corrections and suggestions by the judges. It is important to emphasize that it is the nurse's responsibility to access the gastrointestinal tract via nasogastric or orogastric tube (tube with guidewire introducer, transpyloric or not) (23) . As it is an invasive procedure, adequate placement and subsequent evaluation must be conducted to avoid serious complications, such as inadvertent insertion (2,24) or aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Los cuidadores respondieron un instrumento desarrollado en 2019 por los autores a partir de los marcos teóricos (11)(12)(13)(14)(15)(16) sobre la autopercepción de la adquisición de conocimiento, seguridad, motivación y autoconfianza después de participar en estrategias educativas. El instrumento fue probado previamente con cinco cuidadores, elegidos por conveniencia y que no formaban parte de la muestra y requirió la realización de pequeños ajustes para facilitar la comprensión de los participantes.…”
Section: -2020unclassified